Using administrative data to examine government service transitions of children, youth and young adults in Alberta, Canada - Lamba, Navjot; Jia, Ruiting; Bhatt, Hitesh (International Journal of Population Data Science, 2018)
Introduction A main goal of policy makers is to understand various transition pathways between services to optimize program design and to achieve successful outcomes, for example, securing stable income or having access to disability supports. Objectives and Approach Using linked administrative data (between 2006 and 2011), this study examines two types of program transition pathways: 1) Toward understanding who may be at risk for relying on income support, we profile Albertans transitioning from an income support training program to a program providing income support but no training, and 2) Toward understanding service delivery from child/youth to adult disability programs, we profile students receiving child/youth disability services, but who did not transition into an adult disabilities program. The socio-demographic characteristics and government service use of these students, including health and education-related services, were examined. Results First, among Albertans who transitioned from an income support training program to one in which only income support was provided: 57% were female; 72% were living in low socio-economic neighbourhoods; 14% were high cost health service users; 20% received mental health services; 30% received an injury/harm diagnosis; and 12% were involved in corrections. Second, among children/youth who received child disability services but did not transition to an adult disability program, lower than expected proportions received Assured Income for the Severely Handicapped (45%) and Income Support (14%), while higher than expected proportions had criminal offences (17%). Conclusion/Implications Profiles produced from linked data helps Alberta government to understand clients’ program transitions which allows for: 1) the identification of Albertans requiring supports for securing employment that reduce or eliminate the need for income support, and 2) improvements in service delivery to individuals transitioning from child/youth to adult disability programs.